2018
DOI: 10.6063/motricidade.9343
|View full text |Cite
|
Sign up to set email alerts
|

4-year Longitudinal Study of the Assessment of Body Posture, Back Pain, Postural and Life Habits of Schoolchildren

Abstract: The aim of this study was to evaluate the behaviour of postural variables and the associated factors, like back pain and life habits, in schoolchildren during a period of four years. Forty-two school children underwent a postural assessment using Digital Image-Based Postural Assessment software. They also answered the self-administered questionnaire titled, "Back Pain and Body Posture Evaluation Instrument" to evaluate their back pain and life habits. We observed a significant trend of forward head, thoracic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…Lifetime prevalence of this condition in this age group also varies from 13 to 51% [4]. It is well known that back pain in younger generation might be due to genetics and trunk asymmetry in children and adolescents especially girls as well as several behavioral risk factors including adoption of improper postures during sitting, standing, and lifting heavy objects, carrying heavy backpacks incorrectly, carrying school bags on one side of the body, and sedentary lifestyle [1,3,10].…”
Section: Introductionmentioning
confidence: 99%
“…Lifetime prevalence of this condition in this age group also varies from 13 to 51% [4]. It is well known that back pain in younger generation might be due to genetics and trunk asymmetry in children and adolescents especially girls as well as several behavioral risk factors including adoption of improper postures during sitting, standing, and lifting heavy objects, carrying heavy backpacks incorrectly, carrying school bags on one side of the body, and sedentary lifestyle [1,3,10].…”
Section: Introductionmentioning
confidence: 99%
“…The problematic hips level -one hip was higher than the other -was observed on 52% of all assessed subjects. But Rosa et al, [1], did not fi nd any change by pelvic alignment in frontal plane for schoolchildren.…”
Section: Resultsmentioning
confidence: 89%
“…Neck forward was found among 52% of all children and shoulders forward was exhibited among 51.9%of all children. According to Rosa et al,[1], their study found the forward head position with 66.7% of the schoolboys and 58.3% of the schoolgirls. On the other hand Asl and Savucu[9], found that only 20.6% of male students at the age between 11-16 had forward head.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Although previous studies have investigated a broad range of variables, including biological parameters (such as weight, muscle strength, or ergonomics), psychosocial factors (such as family and societal relationships or satisfaction with school), lifestyle-related variables (such as physical activities [PAs], watching TV, or computer use), and posture, as potential causative factors of LBP in children and teenagers [11][12][13][14][15][16], inconsistent results have been reported regarding these risk factors and their relationships with LBP in children and teenagers. Furthermore, studies that incorporate all the above factors in a single analysis are quite limited [6,7,17].…”
Section: Methodsmentioning
confidence: 99%